2018
DOI: 10.1016/s1473-3099(18)30309-8
|View full text |Cite|
|
Sign up to set email alerts
|

Antimalarial activity of single-dose DSM265, a novel plasmodium dihydroorotate dehydrogenase inhibitor, in patients with uncomplicated Plasmodium falciparum or Plasmodium vivax malaria infection: a proof-of-concept, open-label, phase 2a study

Abstract: SummaryBackgroundDSM265 is a novel, long-duration inhibitor of plasmodium dihydroorotate dehydrogenase (DHODH) with excellent selectivity over human DHODH and activity against blood and liver stages of Plasmodium falciparum. This study aimed to assess the efficacy of DSM265 in patients with P falciparum or Plasmodium vivax malaria infection.MethodsThis proof-of-concept, open-label, phase 2a study was conducted at the Asociación Civil Selva Amazónica in Iquitos, Peru. Patients aged 18–70 years, weighing 45–90 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 19 publications
5
131
0
Order By: Relevance
“…The estimated log 10 PRR 48 in this study is similar to the reported values of chloroquine-sensitive isolates (range 2.6-3.6), 38,39 mefloquine (2.6), 38 and halofantrine (2.3). 38 However, the log 10 PRR 48 estimated for chloroquine is lower than artesunate (3.2), 38 artemether (3.2), 38 artefenomel (range 4.6-6.3), 40 and ganaplacide (range 3.1-3.8), 41 but higher than primaquine (1.0), 38 quinine (2.0), 38 DSM265 (range 0.8-1.5), 42 and sulfadoxine-pyrimethamine (range 1.2-1.5) 38 in patients with P. vivax malaria. Simulations showed that chloroquine efficacy was sensitive to changes in E max CQ.…”
Section: Discussionmentioning
confidence: 96%
“…The estimated log 10 PRR 48 in this study is similar to the reported values of chloroquine-sensitive isolates (range 2.6-3.6), 38,39 mefloquine (2.6), 38 and halofantrine (2.3). 38 However, the log 10 PRR 48 estimated for chloroquine is lower than artesunate (3.2), 38 artemether (3.2), 38 artefenomel (range 4.6-6.3), 40 and ganaplacide (range 3.1-3.8), 41 but higher than primaquine (1.0), 38 quinine (2.0), 38 DSM265 (range 0.8-1.5), 42 and sulfadoxine-pyrimethamine (range 1.2-1.5) 38 in patients with P. vivax malaria. Simulations showed that chloroquine efficacy was sensitive to changes in E max CQ.…”
Section: Discussionmentioning
confidence: 96%
“…Resistance continues to be problematic however, with a number of antimalarials in development yielding resistance readily in culture (Blasco et al, 2017). A recent clinical trial showed that mutations affording moderate resistance to the plasmodial DHODH inhibitor DSM265 were identified in P. falciparum-infected patients who recrudesced following a single dose (Llanos-Cuentas et al, 2018). Resistance also arises readily to another mitochondrial inhibitor, atovaquone, which targets cytochrome b and inhibits electron transport.…”
Section: Implications For Treatment and Future Research Outlookmentioning
confidence: 99%
“…Parasitemia was measured each morning from day 4 until qPCR results became positive and thereafter at 12-h intervals until treatment initiation. Monitoring then occurred pretreatment and at the following time points posttreatment: 2,4,8,12,16,20,24,30,36,48,60,72,84,96,120, and 144 h. Subsequent measurements were approximately three times per week until the end of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies indicated that DSM265 is highly selective toward Plasmodium DHODH and is active against both blood and liver stages of P. falciparum (13). Clinical studies have also been performed which have demonstrated the good tolerability profile of DSM265 in humans and its activity in clearing P. falciparum parasitemia (4,(14)(15)(16).…”
mentioning
confidence: 99%